New Gatekeeper To New Media - خيرة, مكرتار (Université de M'sila, 2020)
New gatekeeper to new Media Presented by : Mokretar Kheira (University of Mostaganem) Abstract This study explores the role of the gatekeeper in disseminating local and national news through social media, studying the role of editors and users in creating news in the community through the use of Facebook and Twitter, the main feature of this new genre is the interaction with editors using social media to identify and distribute stories Through daily monitoring and readers using these networks to read an article, commenting on the news of the day, this study will provide an insight into what users prefer social networking sites, and times when newspapers use of social media to develop news stories, and distributed widely and it will provide insight about the reason for readers to publish their news. Key words: Electronic Press, Electronic Gatekeeper, Social Media, News, Facebook, Twitter.
Keywords: حارس بوابة جديد لإعلام جديد خيرة مكرتار (جامعة مستغانم) ملخص تهدف هذه الدراسة إلى البحث في دور حارس البوابة الالكترونية في تحرير و نشر الأخبار الوطنية و المحلية و ذلك من خلال صفحات الجرائد الالكترونية على مواقع التواصل الاجتماعي، ودراسة دور المحررين والمستخدمين في خلق الأخبار بالمجتمع الافتراضي من خلال موقعي: فيسبوك و تويتر، لما تتميز به هتين الشبكتين من تفاعل و شعبية بين المتصفحين في العالم عموما و الجزائريين خصوصا و بين المحررين للمضامين الاعلامية التي تنشرها الصحف الالكترونية عبر صفحاتها، و ذلك لتحديد وتوزيع القصص من خلال الرصد اليومي لمختلف الأحداث والتعليق على الأخبار الصادرة طيلة اليوم، هذا و تحاول الباحثة من خلال هذه الدراسة تقديم نظرة معمقة لما يفضله مستخدمو مواقع التواصل الاجتماعي، و الأوقات التي تستغلها الصحف لتقديم رسائلها إلى جماهيرها المستهدفة و ذلك من خلال وصف كيف أصبح المحرر يسخر مواقع التواصل الاجتماعي في خدمة و تطوير المحتوى الاعلامي لجريدته الالكترونية. الكلمات الدالة: صحافة الكترونية، مواقع التواصل الاجتماعي، حارس بوابة الكترونية، صفحات الويب، فيسبوك، تويتر.